PODCAST USAGE: EXPANDING ENGLISH LEARNING OF UNDERGRADUATE STUDENT AT UNIVERSITAS AHMAD DAHLAN - Winarko; Sansinadi, Imam Tyas; Wardhany, Dwi Suny (English Education:Journal of English Teaching and Research, 2020)
Podcast is an audio or video program which can be downloaded via the Internet to your mobile phone or computer in the form of an audio or video material. It is an interesting media that some people use to provide and share information. The use of podcast is another enjoyable way to expand the learning of English, as well as the use of movies or music as a mother tongue. This allows both students and teachers to develop their quality of learning. The style can also be more interesting and fun, as students and teachers can explore new ways of learning. This study aims to analyze the benefit of using podcast to enhance English skill for the undergraduate students at Universitas Ahmad Dahlan. The method used in this research is a qualitative approach. The objects of this research are the undergraduate students of Universitas Ahmad Dahlan who have been using a podcast in their daily life. The instruments used in this research are direct observations and semi-structured interview. The process of data analysis is started by collecting data from direct observation and semi-structured interviews. Then, the results of data analysis are integrated into the form of descriptive. The results showed that Podcast's benefits are that it can be downloaded and heard any time and wherever they want. It can be a media to get entertained besides enhancing English skills. Moreover, podcast can develop listening, speaking, pronunciation, as well as vocabulary.